Environmental hazard assessment of a marine mine tailings deposit site and potential implications for deep-sea mining. (September 2017) - Mestre, Nélia C.; Rocha, Thiago L.; Canals, Miquel; Cardoso, Cátia; Danovaro, Roberto; Dell'Anno, Antonio; Gambi, Cristina; Regoli, Francesco; Sanchez-Vidal, Anna; Bebianno, Maria João
Abstract: Portmán Bay is a heavily contaminated area resulting from decades of metal mine tailings disposal, and is considered a suitable shallow-water analogue to investigate the potential ecotoxicological impact of deep-sea mining. Resuspension plumes were artificially created by removing the top layer of the mine tailings deposit by bottom trawling. Mussels were deployed at three sites: i) off the mine tailings deposit area; ii) on the mine tailings deposit beyond the influence from the resuspension plumes; iii) under the influence of the artificially generated resuspension plumes. Surface sediment samples were collected at the same sites for metal analysis and ecotoxicity assessment. Metal concentrations and a battery of biomarkers (oxidative stress, metal exposure, biotransformation and oxidative damage) were measured in different mussel tissues. The environmental hazard posed by the resuspension plumes was investigated by a quantitative weight of evidence (WOE) model that integrated all the data. The resuspension of sediments loaded with metal mine tails demonstrated that chemical contaminants were released by trawling subsequently inducing ecotoxicological impact in mussels' health. Considering as sediment quality guidelines (SQGs) those indicated in Spanish action level B for the disposal of dredged material at sea, the WOE model indicates that the hazard is slight off the mine tailings deposit, moderate on the mine tailings deposit without the influence from the resuspension plumes, and major under the influence of the resuspension plumes. Portmán Bay mine tailings deposit is a by-product of sulphide mining, and despite differences in environmental setting, it can reflect the potential ecotoxic effects to marine fauna from the impact of resuspension of plumes created by deep-sea mining of polymetallic sulphides. A similar approach as in this study could be applied in other areas affected by sediment resuspension and for testing future deep-sea mining sites in order to assess the associated environmental hazards. Graphical abstract: Highlights: Resuspension plumes of Portmán Bay mine tailings deposit were artificially created. Environmental hazard posed by plumes was investigated by a quantitative WOE model. The hazard is major under the influence of resuspension plumes. Plumes from deep-sea mining of polymetallic sulphides may cause similar hazards. A similar approach could be applied to deep-sea mining. Abstract : Sediment resuspension plumes on a sulphide mine tailings deposit cause major environmental hazard. Similar hazard may be expected in plumes from deep-sea mining.